2017
DOI: 10.20408/jti.2017.30.4.192
|View full text |Cite
|
Sign up to set email alerts
|

Management of High-grade Blunt Renal Trauma

Abstract: Purpose: Blunt injury accounts for 80-95% of renal injury trauma in the United States. The majority of blunt renal injuries are low grade and 80-85% of these injuries can be managed conservatively. However, there is a debate on the management of patients with high-grade renal injury. We reviewed our experience of renal trauma at our trauma center to assess management strategy for high-grade blunt renal injury. Methods: We reviewed blunt renal injury cases admitted at a single trauma center between August 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Blunt trauma to the abdomen, flank, or back is the most common mechanism of injury [1]. Blunt trauma is reported to be the cause of the majority of cases (80-95% of all renal trauma) and mostly occurs due to traffic accidents [6,11]. However, in the military community and large cities, the prevalence of penetrant renal trauma can reach 20% or more [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blunt trauma to the abdomen, flank, or back is the most common mechanism of injury [1]. Blunt trauma is reported to be the cause of the majority of cases (80-95% of all renal trauma) and mostly occurs due to traffic accidents [6,11]. However, in the military community and large cities, the prevalence of penetrant renal trauma can reach 20% or more [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the military community and large cities, the prevalence of penetrant renal trauma can reach 20% or more [8]. Many blunt renal traumas are in the low-grade classification, and 80-85% of these cases can be treated with non-operative management (NOM) [11]. Renal trauma is often associated with injury to other major organs [5] and occurs in 3% of patients who are hospitalized due to trauma [10].…”
Section: Introductionmentioning
confidence: 99%
“…There is a trend towards the increased use of AE in trauma in general and in renal injury in particular which will reduce the need for nephrectomy. 10 A survey of clinicians' practices revealed that AE is regularly used in low-grade renal injuries 11 ; however, the appropriateness has been questioned due to good outcomes with conservative management. 12 Its use in high-grade renal injuries is now well established although there are some studies that report a high failure rate with Grade V injuries.…”
Section: Centralisation Of Servicesmentioning
confidence: 99%
“…Trauma due to falling from a height or severe physical injury (blunt/non-penetrating trauma) has been reported as the cause of 80-95% of renal injury, which often occurs due to road accidents (12)(13)(14). The average severity of injury in patients with renal injury was significantly higher in comparison to people with injury to other organs (4).…”
Section: Introductionmentioning
confidence: 99%